2014
DOI: 10.1136/bmjopen-2013-004062
|View full text |Cite
|
Sign up to set email alerts
|

Sensitisation to mites in a group of patients with asthma in Yaounde, Cameroon: a cross-sectional study

Abstract: ObjectivesSensitisation of asthmatic patients to mites in sub-Saharan Africa has been less described. The aim of this study was to assess the prevalence and determinants of sensitisation to mites in asthmatic adolescents and adults in Yaounde, Cameroon.DesignThis was a cross-sectional study. Logistic regression models were employed to investigate the determinants of sensitisation to mites.SettingThis study was carried out at the Jamot Hospital and CEDIMER private centre, in Yaounde, capital city of Cameroon.Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…In the case of the former, however, differences in cavitation, which is largely immune-mediated, may be difficult to detect due to smoking-related pulmonary immune dysfunction; irrespective of this caveat, a previous study involving 13,088 cases of pulmonary TB has, however, documented more severe cavitary disease in smokers 6 . With respect to culture conversion, delayed sputum conversion in smokers has also been reported in several studies [27][28][29] . Follow-up studies may also identify the relative contributions of infection and smoking to the observed alterations in vitamin C status.…”
Section: Discussionmentioning
confidence: 53%
“…In the case of the former, however, differences in cavitation, which is largely immune-mediated, may be difficult to detect due to smoking-related pulmonary immune dysfunction; irrespective of this caveat, a previous study involving 13,088 cases of pulmonary TB has, however, documented more severe cavitary disease in smokers 6 . With respect to culture conversion, delayed sputum conversion in smokers has also been reported in several studies [27][28][29] . Follow-up studies may also identify the relative contributions of infection and smoking to the observed alterations in vitamin C status.…”
Section: Discussionmentioning
confidence: 53%
“…In addition to the medical history and clinical examination, SPT and determination of allergen-specific IgE are the leading diag- (12,14,(16)(17)(18)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the etiology of AA and allergic sensitization, it is essential to investigate patients' homes for HDM and to concomitantly conduct skin and serological tests (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Les travaux antérieurs réalisés sur les acariens dans ces pays aux ressources limitées ne sont pas nombreux. Quelques-uns ont été effectués dans certaines villes d'Afrique subsaharienne et ont retrouvé des fréquences élevées de sensibilisation aux acariens, que ce soit dans la population générale ou chez des patients suivis pour des manifestations d'ordre allergique [12][13][14].…”
Section: Introductionunclassified
“…Cependant, il a été difficile, faute de tests moléculaires de conclure à une co-sensibilisation ou plutôt à des réactions croisées entre des espèces ou des familles d'acariens[9]. Un pourcentage légèrement plus élevé a été retrouvé à Yaoundé parmi des asthmatiques suivis, 34,8%[13]. Une telle sensibilisation est aussi fréquente en population générale ; elle était de 14,5% parmi des jeunes adultes dans un travail réalisé à Douala par Mbatchou et al[12].…”
unclassified